Indigenous knowledge and uses of Ficus species in the Sudanian zone of Burkina Faso: Prospects for sustainable management of their natural resources - Sawadogo, Youssouf; Sabo, Prospère; Zon, Aboubacar-Oumar; Kabré, Blaise; Belem, Mamounata; Ouédraogo, Amadé (Ethnobotany Research and Applications, 2025)
Background: In Burkina Faso, Ficus is one of the largest plant genera. However, its resource availability, populations status and uses which are crucial for the conservation of the species have not been sufficiently documented. This study aims to fill this gap of knowledge. Methods: Semi-structured interviews were carried out purposively from August 2021 to April 2022 with 240 informants of different age categories, ethnic groups and sexes across 12 villages in the Sudanian zone of Burkina Faso. Collected information related to the resource availability, the population status and the uses of Ficus species. The data analysis consisted of calculation of frequencies and ethnobotanic indices such as relative frequency of citation (RFC) and use value. Chi-squared test and generalized linear model were used for statistical comparisons. Results: Ficus species resources were perceived to be rare (69.06%) while populations status was perceived to be declining (41.39%). Both resource availability and populations status were only influenced by the ethnic group (p-value < 0.05). The most useful species were F. sycomorus, F. platyphylla and F. sur. Species were mostly used in medicine (RFC = 91.25%), fodder (90%), food (84.58%) and firewood (79.16%). Uses were strongly influenced by informants’ ethnic group (p-value = 0.002), sex (p-value = 8.75e-06) and age category (p-value = 0.001). Conclusions: The global decline trend of Ficus species in Burkina Faso combined with their high use by populations suggest the necessity of implementing conservation strategies involving the local population. Keywords: Locals’ perceptions, Ficus species diversity, Fig tree uses, Plant use value Résumé Contexte : Au Burkina Faso, les Ficus constituent l’un des genres les plus représentatifs de la flore. Cependant, la disponibilité des ressources, la dynamique des populations et les pratiques d’utilisations qui sont cruciaux pour la conservation du taxon n’ont pas été suffisamment documentés. Cette étude vise à combler ce manque de connaissances. Méthodes : Des entretiens semi-structurés ont été menés aléatoirement du mois d’août 2021 au mois d’avril 2022 avec 240 informateurs de différentes classes d’âge, groupes ethniques et sexes dans 12 villages de la zone soudanienne du Burkina Faso. Les informations recueillies ont porté sur la disponibilité des ressources, la dynamique des populations et les usages des espèces. L’analyse des données a consisté au calcul de fréquences et d’indices ethnobotaniques tels que la fréquence relative de citation (FRC) et la valeur d’usage. Le test du Khi-deux et le modèle linéaire généralisé ont été utilisés pour les comparaisons statistiques. Résultats : Les perceptions des enquêtés ont montré que les ressources des Ficus sont rares (69,06 %), tandis que la dynamique des populations est régressive (41,39 %). La disponibilité des ressources et la dynamique des populations sont influencées uniquement par le groupe ethnique (p-value < 0,05). Les espèces les plus importantes sont F. sycomorus, F. platyphylla et F. sur. Les espèces de Ficus sont principalement utilisées en médecine (FRC = 91,25%), comme fourrage (90%), en alimentation (84,58%) et comme bois de chauffe (79,16%). Les usages sont significativement influencés par le groupe ethnique (p-value = 0,002), le sexe (valeur p-value 0,001) et la classe d’âge (p-value = 0,001). Conclusion : La dynamique régressive des espèces de Ficus au Burkina Faso, combinée à leur forte utilisation par les populations, suggère la nécessité de mettre en place des stratégies de conservation impliquant les populations locales. Mots-clés : Perceptions des populations locales, diversité des espèces de Ficus, usages du figuier, valeur d’usage des plantes.